A New design of fuzzy logic controller optimized By PSO-SCSO applied To SFO-DTC induction motor drive - Ali Taieb; Abdellaziz Ferdjouni (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this paper, a new strategy for the design of fuzzy logic controllers (FLC) is proposed. This strategy is based on the optimization, by the particle swarm optimization (PSO) Algorithm and by sine-cosine based swarm optimization (SCSO) Algorithm, of the input-output gains and the geometric forms of the triangular membership functions of the proposed FLC. This latter is obtained by the minimizing a cost function based on combining two criterions, the Integral Time Absolute Error (ITAE) and Integral Absolute Error (IAE). A comparison, between the conventional FLC and the proposed FLC is carried out. The PSO-FLC shows a remarkable improvement in the performances of the controlled induction motor.